Yugoslavia and the Balkan unity, 1925–1930 - Mićić, Srđan (Balcanica Posnaniensia. Acta et studia, 2022)
This paper analyzes policies of the Yugoslav foreign ministers Momčilo Ninčić and Vojislav Marinković towards the ideas of the Balkan unity. Not only were both of them prominent political figures, but also economists and in several mandates ministers of finance, national economy, trade (and industry) and/or construction. Therefore the aim is to analyze their views on the political unification and economic co-operation between the Balkan states, and factors that provided opportunities or stood as constraints to the implementation of their plans. Chronologically, the paper covers the period from the beginning of the Locarno period in the Balkans to the beginning of the Balkan Conferences. The paper is primarily based on the Yugoslav and Bulgarian archival sources, domestic and foreign published sources, and scientific literature.